2012
DOI: 10.1080/19361521.2012.646413
|View full text |Cite
|
Sign up to set email alerts
|

Trauma Exposure, Psychosocial Functioning, and Treatment Needs of Youth in Residential Care: Preliminary Findings from the NCTSN Core Data Set

Abstract: InitiativeGiven the high prevalence rates of trauma exposure in youth in residential treatment, evidence-based guidelines are needed to identify youth most likely to benefit from this setting. We examined trauma exposure, functional impairments, and treatment outcomes in a large clinical dataset. When compared to youth in nonresidential settings (n = 9,942), youth in residential settings (n = 525) reported both higher rates of trauma exposure across types and higher rates of impairments. Moreover, as the numbe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
94
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 164 publications
(98 citation statements)
references
References 25 publications
2
94
0
2
Order By: Relevance
“…Findings from the Adverse Childhood Experiences (ACE) studies demonstrate a graded relationship between number of adverse childhood experiences and significant adult physical health and mental health problems (Anda et al 2006;Fellitti and Anda 2010). This finding is echoed in recent studies of youth in residential treatment in which the number of types of traumas were positively correlated with breadth and depth of symptomatology, functional impairment (Briggs et al 2012), and treatment response (Boyer et al 2009). …”
mentioning
confidence: 56%
See 2 more Smart Citations
“…Findings from the Adverse Childhood Experiences (ACE) studies demonstrate a graded relationship between number of adverse childhood experiences and significant adult physical health and mental health problems (Anda et al 2006;Fellitti and Anda 2010). This finding is echoed in recent studies of youth in residential treatment in which the number of types of traumas were positively correlated with breadth and depth of symptomatology, functional impairment (Briggs et al 2012), and treatment response (Boyer et al 2009). …”
mentioning
confidence: 56%
“…The equivocal findings on the effectiveness of residential treatment for youth suggest that further parsing out of etiology, diagnosis, and treatment focus and approach is warranted (Boyer et al 2009;Briggs et al 2012). Findings from the Adverse Childhood Experiences (ACE) studies demonstrate a graded relationship between number of adverse childhood experiences and significant adult physical health and mental health problems (Anda et al 2006;Fellitti and Anda 2010).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The CDS includes information on demographics, family characteristics, service use, trauma exposure, functioning, and standardized assessments of emotional-behavioral problems. NCTSN procedures for gathering CDS data are described in detail elsewhere (Briggs et al, 2012;Layne et al, 2014).…”
Section: Methodsmentioning
confidence: 99%
“…For example, through analysis of one of the world's largest child trauma databases, our colleagues at National Center for Child Traumatic Stress (NCCTS) have demonstrated that youth in residential treatment settings constitute the most vulnerable subgroup of children and adolescents victimized by trauma, exhibiting the highest rates of trauma exposure, associated impairment, and need for extensive intervention (Briggs et al 2012). Just as often, however, out-of-home placement decisions are seemingly "the luck of the draw," predicated upon local resources and capacity, and in many instances ultimately decided by whoever happens to be next in line for an available bed.…”
mentioning
confidence: 99%